(untitled) (Archives of Clinical Psychiatry, 2003)
The authors talk about the characteristics of the schizophrenic forms called by Kleist as the confusional group, differentiating it from the paranoid group. They present four cases that, according to the systematization made by Aníbal Silveira, were considered initially as the forms of the confusional group of schizophrenia: Incoherent, Paralogical, Phantasiophrenia and Schizophasia. From a cognitive-systemic perspective, supported by concepts of the neuro-psychology, an analysis of the cognitive processes of each patient was presented and studied through the psychodiagnostic of Rorschach, emphasizing the alterations related to the different psychic systems, characteristic of each case. Their goal is to make evident that the psychic examination through the Rorschach test can contribute for the experimental study of the mental processes and its different forms of implications.